AKR1C3 in carcinomas: from multifaceted roles to therapeutic strategies - Li, Mengnan; Zhang, Limin; Yu, Jiahui; Wang, Xiaoxiao; Cheng, Le; Ma, Zhaowu; Chen, Xiaoguang; Wang, Lingzhi; Goh, Boon Cher (Frontiers in Pharmacology, 2024)
On line 441, imatinib is not appropriate to use an abbreviation format (IM)Response: We have changed the abbreviation format of imatinib to its full name on lines 451, 453, 455.Together, we have diligently incorporated all revisions in accordance with the feedback provided. We firmly believe that these enhancements have substantially improved the quality of our manuscript, and we trust they align with your expectations. We extend our gratitude for the constructive comments and valuable suggestions provided by the editors and reviewers. Your efforts in reevaluating our work are greatly appreciated. We eagerly anticipate your favorable response.